Pengabdian Manajemen Kebersihan Masjid Melalui Karang Taruna Melatinyawiji di Desa Nambangrejo Kecamatan Sukorejo - Santoso, Riko Muhammad; Ahrori, Moh. Hazim (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Nambangrejo Village, Sukorejo District, especially in RT1/RW1, there is a Melatinyawiji Karang Taruna organization where the community really wants its activity to be effective in environmental activities such as being active in the scope of cleaning the mosque, which is the main activity of the Karang Taruna. In carrying out mosque cleaning activities there are problems such as the lack of cleaning equipment and also the activeness of youth organization members, this has a big impact on social welfare in the environment. In this service process, the aim is to increase and also develop the potential of the members of the Melatinyawiji youth organization in effectively carrying out community activities in terms of cleanliness management of the Darul Ikhsan mosque. This service uses direct action research in the field and also through interviews in order to obtain the data needed to deal with existing problems. The result of this service is that the Melatinyawiji Youth Organization has good management in carrying out the community's social activities and also in this service the members of KPM INSURI Ponorogo are very helpful in implementing existing activities according to what has been designed in the process of managing the cleanliness of the Darul Ikhsan Mosque.